A passive stress-based method for universal bonding of ceramic materials
Patent Information
- Application Number
- CN202411412973.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-10-11
AI Technical Summary
In existing technologies, the connection method for high-temperature and high-pressure equipment still relies on the ceramic material connection method for transmission, which requires high temperature and high pressure conditions, resulting in high connection costs and making it difficult to achieve industrial production of large-size and complex-shaped ceramic parts.
C/C flat plates and low thermal expansion coefficient plates are used to clamp the stacked ceramic parts to be connected, and C/C bolts are used to fix them. The connection is achieved by generating thermal stress through the difference in thermal expansion coefficients, which replaces the pressure provided by traditional high-pressure equipment.
It reduces the dependence on connecting pressure equipment, lowers the connection cost, and enables universal connection of various ceramic materials by adjusting the clamping plate material and connecting slurry. The ceramic connector has excellent bending strength and acid and alkali corrosion resistance.
Smart Images

Figure CN119430981B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of ceramic component connection methods, and relates to a universal connection method for ceramic materials based on passive pressure. Background Technology
[0002] Ceramic materials possess excellent high-temperature strength, low coefficient of thermal expansion, superior thermal shock resistance, corrosion resistance, and wear resistance, making them widely used in aerospace, petroleum, chemical, and machinery industries, and they are currently receiving increasing attention. With the rapid development of aerospace, defense, and automotive sectors, there is an urgent need for larger and more complex advanced ceramic material structural components. However, the high brittleness, low ductility, and high hardness of ceramic materials result in poor machinability, making the fabrication of large and complex silicon carbide components difficult and costly under current industrial development levels. Joining simple ceramic components using joining technologies is an effective method, and advanced joining technologies make it possible to manufacture large and complex-shaped ceramic material components, which is of great significance to industrial development.
[0003] A good bonding interface should maximize the continuity of its basic physicochemical properties (lattice structure, thermal conductivity, electrical conductivity, coefficient of thermal expansion), mechanical behavior (no significant change in elastic modulus), and thermodynamic stability (no interface reaction during application). Therefore, the development direction of ceramic bonding will focus on bonding material systems where the bonding layer product is homogeneous with the matrix material. Currently, the diffusion welding method is widely used, which stacks ceramic parts to be bonded and achieves homogeneous bonding under high pressure of 2000–2400℃ and 20–25 MPa. To reduce the bonding temperature, researchers have developed the nano-impregnation transient liquid phase (NITE) bonding method, using nanoparticles homogeneous with the matrix as raw materials and combining them with sintering aids to achieve high-density bonding of ceramics under certain pressure. Subsequently, Northwestern Polytechnical University proposed a novel electric field-induced flash joining (FJ) technology, which can bond ceramic materials in an extremely short time (seconds) by applying a DC electric field exceeding the threshold to ion-conductive ceramic materials. Researchers have achieved seamless bonding of SiC ceramics by forming a liquid phase at the interface between Dy3Si2C2 and SiC and extruding it under pressure. However, bonding methods such as diffusion welding, NITE bonding, electric field-assisted bonding, and flash burning are extremely demanding, typically requiring high temperature (≥1800℃) and high pressure (≥10MPa) processes. These methods rely on pressure equipment to provide active pressure, which greatly increases the bonding cost and makes industrial-scale production difficult. Summary of the Invention
[0004] The purpose of this invention is to address the aforementioned problems in the prior art by proposing a universal ceramic material connection method based on passive pressure, which uses C / C flat plates and low thermal expansion coefficient flat plates to clamp stacked ceramic parts to be connected and fixes them with C / C bolts. This method results in ceramic connectors with better bending strength and resistance to acid and alkali corrosion.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] A universal joining method for ceramic materials based on passive pressure, the joining method comprising:
[0007] After coating the surface of the first ceramic part with a connecting slurry, the second ceramic part is placed on it and stacked in a sandwich structure of first ceramic part-connecting slurry-second ceramic part. Low thermal expansion coefficient C / C plate and differential thermal expansion coefficient plate are used to clamp the sandwich structure on both sides, and low thermal expansion coefficient C / C bolts are used to fix it. Then, sintering is performed to achieve the connection.
[0008] The coefficient of thermal expansion of the differentially thermally expanded plate is 0.1 × 10⁻⁶. -6 ~30×10 -6 / ℃, the coefficient of thermal expansion of C / C bolts is 0~2×10. -6 / ℃.
[0009] Preferably, the coefficient of thermal expansion of the C / C bolt is 0 to 1×10⁻⁶. -6 / ℃.
[0010] As a preferred embodiment, after clamping the sandwich structure with low thermal expansion coefficient C / C plates and differential thermal expansion coefficient plates on both sides and fixing them with low thermal expansion coefficient C / C bolts, the preload of the bolts clamping and fastening the two plates is 20 to 30 N·m.
[0011] Preferably, during the sintering process, the thermal stress of the sandwich structure of the first ceramic part-connecting slurry-second ceramic part is 0.5 to 5 GPa.
[0012] Preferably, the plate with differentiated thermal expansion coefficient includes one or more of graphite plate, alumina ceramic plate, silicon carbide ceramic plate, and titanium boride ceramic plate.
[0013] Further optimization yields a graphite plate with a coefficient of thermal expansion of 5 × 10⁻⁶. -6 ~25×10 -6 / ℃;
[0014] The coefficient of thermal expansion of the alumina ceramic plate is 5.5 × 10⁻⁶. -6 ~8.9×10 -6 / ℃; the coefficient of thermal expansion of the silicon carbide ceramic plate is 4.4×10.-6 ~6.5×10 -6 / ℃;
[0015] The coefficient of thermal expansion of the titanium boride ceramic plate is 6.1 × 10⁻⁶. -6 ~8.2×10 -6 / ℃.
[0016] Preferably, the coefficient of thermal expansion of the C / C plate is 0 to 5 × 10⁻⁶. -6 / ℃.
[0017] Preferably, the thickness of the plate with the differential thermal expansion coefficient is 1 to 130 mm, and its length and width are both greater than those of the first ceramic part and the second ceramic part.
[0018] Further optimization is made by using a plate with a differential coefficient of thermal expansion with a thickness of 10–50 mm.
[0019] Preferably, the thickness of the C / C plate is 1 to 130 mm, and its length and width are both greater than those of the first ceramic part and the second ceramic part.
[0020] Further optimization is that the thickness of the C / C plate is 10–50 mm.
[0021] Preferably, the first ceramic component and the second ceramic component are independently selected from one or more of oxide ceramics, carbide ceramics, and boride ceramics.
[0022] Preferably, the bonding slurry includes ceramic powder, sintering aid, dispersant, binder, and solvent.
[0023] Further preferred, the bonding slurry comprises ceramic powder, sintering aid, dispersant, binder and solvent in a mass ratio of (40-70):(1-12):(0.8-6):(0.1-1.4):(45-80).
[0024] Further preferred, the solid content of the bonding slurry is 30–70 wt%.
[0025] More preferably, the solid content of the bonding slurry is 45-60 wt%.
[0026] Further optimization yields ceramic powder with an average particle size of 1–200 nm.
[0027] Further preferably, the dispersant includes one or more of polyvinylpyrrolidone, polyacrylamide, and phosphate; the binder includes one or more of polyvinyl alcohol, polyvinyl butyral, and phenolic resin; and the solvent includes one or more of distilled water, anhydrous ethanol, ethylene glycol, and acetone.
[0028] Further preferably, the sintering aid includes one or more of B4C, carbon black, Al2O3, MgO, Y2O3, Al2O3-Y2O3, AlN, Al4C3-B4C, Al4SiC4, and borax. Further preferably, when the ceramic part is silicon carbide ceramic, the ceramic powder is silicon carbide powder; when the ceramic part is boron carbide ceramic, the ceramic powder is boron carbide powder; when the ceramic part is alumina ceramic, the ceramic powder is alumina powder; and when the ceramic part is titanium diboride ceramic, the ceramic powder is titanium diboride powder.
[0029] Preferably, the sintering temperature is 1000–2200℃ and the sintering time is 0.1–10h.
[0030] Further optimization involves a sintering temperature of 1400–2100℃ and a sintering time of 0.5–5h.
[0031] Preferably, the universal bonding method for ceramic materials based on passive pressure includes:
[0032] (1) Mix silicon carbide powder, sintering aid, dispersant, binder and solvent and ball mill to make slurry, so as to obtain a bonding slurry with a solid content of 45 to 60 wt%;
[0033] (2) Two silicon carbide ceramics are ultrasonically cleaned and dried to serve as the first and second ceramic parts. After coating the surface of the first ceramic part with a connecting slurry, the second ceramic part is placed on top. The ceramic parts are stacked in a sandwich structure of first ceramic part-connecting slurry-second ceramic part. C / C plates and low thermal expansion coefficient plates are used to clamp the sandwich structure on both sides, and C / C bolts are used for fixation. The thermal expansion coefficient of the differential thermal expansion coefficient plate is 0.1×10⁻⁶. -6 ~30×10 -6 / ℃, the coefficient of thermal expansion of C / C bolts is 0~2×10. -6 / ℃; then sinter at 1700~1900℃ for 0.5~2h in an inert gas to achieve bonding.
[0034] Preferably, the universal bonding method for ceramic materials based on passive pressure includes:
[0035] (1) Mix alumina powder, sintering aid, dispersant, binder and solvent and ball mill to make a slurry, so as to obtain a bonding slurry with a solid content of 45 to 60 wt%;
[0036] (2) The alumina ceramic is ultrasonically cleaned and dried to serve as the first ceramic part and the second ceramic part. After coating the surface of the first ceramic part with a connecting slurry, the second ceramic part is placed on top. The ceramic parts are stacked in a sandwich structure of first ceramic part-connecting slurry-second ceramic part. C / C plates and low thermal expansion coefficient plates are used to clamp the sandwich structure on both sides, and C / C bolts are used for fixation. The thermal expansion coefficient of the low thermal expansion coefficient plate is 0.1×10⁻⁶. -6 ~10×10 -6 At / ℃, the coefficient of thermal expansion of C / C bolts is 0~2×10⁻⁶. -6 / ℃; then sinter at 1400~1700℃ for 0.5~2h in an inert gas to achieve bonding.
[0037] Preferably, the universal bonding method for ceramic materials based on passive pressure includes:
[0038] (1) Mix boron carbide powder, sintering aid, dispersant, binder and solvent and ball mill to make slurry, so as to obtain a bonding slurry with a solid content of 45 to 60 wt%;
[0039] (2) Two boron carbide ceramics are ultrasonically cleaned and dried to serve as the first and second ceramic parts. After coating the surface of the first ceramic part with a connecting slurry, the second ceramic part is placed on top. The ceramic parts are stacked in a sandwich structure of first ceramic part-connecting slurry-second ceramic part. C / C plates and low thermal expansion coefficient plates are used to clamp the sandwich structure on both sides, and C / C bolts are used for fixation. The thermal expansion coefficient of the low thermal expansion coefficient plate is 0.1×10⁻⁶. -6 ~10×10 -6 At / ℃, the coefficient of thermal expansion of C / C bolts is 0~2×10⁻⁶. -6 / ℃; then sinter at 1950~2100℃ for 0.5~2h in an inert gas to achieve bonding.
[0040] Preferably, the universal bonding method for ceramic materials based on passive pressure includes:
[0041] (1) Titanium diboride powder, sintering aid, dispersant, binder and solvent are mixed and ball-milled to make a slurry with a solid content of 45 to 60 wt%;
[0042] (2) Two titanium diboride ceramics are ultrasonically cleaned and dried to serve as the first ceramic part and the second ceramic part, respectively. After coating the surface of the first ceramic part with a connecting slurry, the second ceramic part is placed on top. The ceramic parts are stacked in a sandwich structure of first ceramic part-connecting slurry-second ceramic part. C / C plates and low thermal expansion coefficient plates are used to clamp the sandwich structure on both sides, and C / C bolts are used for fixing. The thermal expansion coefficient of the low thermal expansion coefficient plate is 0.1×10⁻⁶. -6 ~10×10 -6At / ℃, the coefficient of thermal expansion of C / C bolts is 0~2×10⁻⁶. -6 / ℃; then sinter at 1750~2000℃ for 0.5~2h in an inert gas to achieve bonding.
[0043] A ceramic connector includes a first ceramic component, an intermediate connecting layer, and a second ceramic component, wherein the thickness of the intermediate connecting layer is 0.1–80 μm.
[0044] Preferably, the thickness of the intermediate connecting layer is 1–45 μm.
[0045] Further preferred, the thickness of the intermediate connecting layer is 4–30 μm.
[0046] Preferably, the weight loss of the intermediate connecting layer after etching with 6 mol / L NaOH solution at 100℃ for 24 hours is <30 mg / dm³. 2 The intermediate bonding layer lost less than 7 mg / dm³ after being corroded by a 3 mol / L sulfuric acid solution at 100°C for 24 hours. 2 .
[0047] Preferably, the intermediate connecting layer of the ceramic connector has a flexural strength of 120–550 MPa at room temperature and a flexural strength of 80–520 MPa at 1400°C.
[0048] Preferably, the intermediate connecting layer of the silicon carbide ceramic connector has a flexural strength of 280–550 MPa at room temperature and a flexural strength of 240–520 MPa at 1400°C.
[0049] Preferably, the intermediate connecting layer of the alumina ceramic connector has a flexural strength of 330–450 MPa at room temperature and a flexural strength of 240–370 MPa at 1400°C.
[0050] Preferably, the intermediate connecting layer of the boron carbide ceramic connector has a flexural strength of 400–470 MPa at room temperature and a flexural strength of 370–420 MPa at 1400°C.
[0051] Preferably, the intermediate connecting layer of the titanium diboride ceramic connector has a bending strength of 120–220 MPa at room temperature and a bending strength of 80–180 MPa at 1400°C.
[0052] Applications of a ceramic connector in aerospace, chemical, heat exchanger packaging, semiconductor, chemical coating, refractory materials, cutting tools, and electronic devices.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] 1. In this invention, flat plates with different coefficients of thermal expansion are used to clamp the sandwich structure of the first ceramic component, connecting slurry, and second ceramic component and are fixed with C / C bolts. The thermal stress generated by the limited thermal expansion of the ceramic component itself and the flat plate clamps with different coefficients of thermal expansion at high temperature replaces the pressure provided by traditional high-pressure equipment, greatly reducing the dependence on connecting pressure equipment and reducing the connection cost.
[0055] 2. Compared with traditional graphite clamping, the clamping device of the present invention generates GPa-level thermal stress at high temperature, which can effectively reduce the sintering temperature of ceramic connectors without the need for external pressure.
[0056] 3. The ceramic powder in the bonding slurry of the present invention has a smaller particle size, which further reduces the sintering temperature of the ceramic connector during the bonding process.
[0057] 4. This invention can meet the connection requirements of various ceramic materials such as oxides, carbides, and borides by adjusting the clamping plate material, the connecting slurry, and the connection temperature, and has universal applicability.
[0058] 5. The intermediate connecting layer of the ceramic connector of the present invention is relatively thin, with excellent connection performance and good resistance to acid and alkali corrosion. Attached Figure Description
[0059] Figure 1 The diagram shows the universal connection method for ceramic materials based on passive pressure according to the present invention (a) and the thermal stress distribution diagram based on COMSOL simulation in Example 1 (b).
[0060] Figure 2 This is a microstructure diagram of the silicon carbide ceramic connector in Embodiment 2 of the present invention.
[0061] Figure 3 This is a conventional graphite fixture used in Comparative Example 1 of the present invention. Detailed Implementation
[0062] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0063] Unless otherwise specified, the materials used in this invention are commercially available products, and the methods used are conventional technical means.
[0064] The differential thermal expansion coefficient plate used in this invention includes one or more of graphite plates, alumina ceramic plates, silicon carbide ceramic plates, and titanium boride ceramic plates; wherein the thermal expansion coefficient of the graphite plate is 5 × 10⁻⁶. -6 ~25×10 -6 / ℃; the coefficient of thermal expansion of the alumina ceramic plate is 5.5×10. -6 ~8.9×10-6 / ℃; the coefficient of thermal expansion of the silicon carbide ceramic plate is 4.4×10. -6 ~6.5×10 -6 / ℃; the coefficient of thermal expansion of the titanium boride ceramic plate is 6.1×10⁻⁶. -6 ~8.2×10 -6 / ℃.
[0065] The coefficient of thermal expansion of C / C flat plates is 0~5×10⁻⁶. -6 / ℃;
[0066] The length and width of the plate with the differential thermal expansion coefficient and the C / C plate are both greater than those of the first ceramic part and the second ceramic part.
[0067] The thickness of the first ceramic part and the second ceramic part used in this invention is 10-30mm.
[0068] The test standard for the bending strength of this invention is GB / T6569-2006 / ISO14704:2000.
[0069] Example 1
[0070] The universal bonding method for ceramic materials based on passive pressure in this embodiment includes the following steps:
[0071] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first and second ceramic parts. A bonding slurry was obtained by ball milling a mixture of 45g silicon carbide powder (average particle size 40nm), 5g Al2O3-Y2O3 (YAG) sintering aid, 2g polyvinylpyrrolidone, 0.5g polyvinyl butyral, and 50g ethanol for 6 hours. The bonding slurry was then applied to the surfaces of the first and second ceramic parts using screen printing. The ceramic parts were stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part, with a 10mm thick C / C plate and a 10mm thick graphite plate clamping each side of the sandwich structure. A material with a thermal expansion coefficient of 0.5 × 10⁻⁶ was then used. -6 The C / C bolts at / ℃ are clamped and fixed with a preload of 25Nm, and then placed in a high-temperature sintering furnace. The ceramic connection is achieved by sintering at 1850℃ for 1 hour in an argon atmosphere to obtain a ceramic connector.
[0072] Figure 1 The diagram (a) shows the universal connection method for ceramic materials based on passive pressure in this embodiment, and the thermal stress distribution diagram based on COMSOL simulation of the connection process in this embodiment 1. It can be seen that during the sintering process, the thermal stress range of the connection contact surface reaches 2.56 to 4.72 GPa.
[0073] The intermediate connecting layer of this silicon carbide ceramic connector has a thickness of 5 μm, a flexural strength of 281 MPa at room temperature, and a flexural strength of 240 MPa at 1400 °C. The ceramic joint (intermediate connecting layer) exhibits a weight loss of 25 mg / dm³ after corrosion with a 6 mol / L NaOH solution at 100 °C for 24 h. 2 After corrosion by 3 mol / L sulfuric acid solution at 100℃ for 24 hours, the weight loss rate was 5 mg / dm³. 2 .
[0074] The silicon carbide ceramic connector in this embodiment can be widely used in aerospace, chemical and heat exchanger packaging fields.
[0075] Example 2
[0076] The universal bonding method for ceramic materials based on passive pressure in this embodiment includes the following steps:
[0077] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first and second ceramic parts. A bonding slurry was obtained by ball milling a mixture of 45g silicon carbide powder (average particle size 40nm), 5g Al4SiC4 sintering aid, 2g polyvinylpyrrolidone, 0.5g polyvinyl butyral, and 50g ethanol for 6 hours. The bonding slurry was then applied to the surface of the first ceramic part using screen printing. The ceramic parts were stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part, with a 10mm thick C / C plate and a 10mm thick graphite plate clamping each side of the sandwich structure. A material with a thermal expansion coefficient of 0.5 × 10⁻⁶ was then used. -6 The C / C bolts at / ℃ are clamped and fixed with a preload of 25 N·m. Then, they are placed in a high-temperature sintering furnace and sintered at 1950℃ for 1 hour in an argon atmosphere to achieve ceramic connection, thus obtaining ceramic connectors.
[0078] The microstructure diagram of the silicon carbide ceramic connector in this embodiment is as follows: Figure 2 As shown, the intermediate connecting layer of this silicon carbide ceramic connector has a thickness of 10.6 μm, a flexural strength of 375 MPa at room temperature, and a flexural strength of 310 MPa at 1400 °C. The ceramic joint exhibits a weight loss of 5 mg / dm³ after corrosion with a 6 mol / L NaOH solution at 100 °C for 24 h. 2 After corrosion by 3 mol / L sulfuric acid solution at 100℃ for 24 hours, the weight loss rate was 2 mg / dm³. 2 .
[0079] The silicon carbide ceramic connector in this embodiment can be widely used in aerospace, chemical and heat exchanger packaging fields.
[0080] Example 3
[0081] The universal bonding method for ceramic materials based on passive pressure in this embodiment includes the following steps:
[0082] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first and second ceramic parts. A bonding slurry was obtained by ball milling 45g of silicon carbide powder (average particle size 40nm), 5g of Al4SiC4 sintering aid, 2g of polyvinylpyrrolidone, 0.5g of polyvinyl butyral, and 50g of ethanol for 6 hours. The bonding slurry was then applied to the surface of the first ceramic part using screen printing. The ceramic parts were stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part, with a 10mm thick C / C plate and a 30mm thick graphite plate clamping each side of the sandwich structure. A material with a thermal expansion coefficient of 0.5 × 10⁻⁶ was then used. -6 The C / C bolts at / ℃ are clamped and fixed with a preload of 25 N·m. Then, they are placed in a high-temperature sintering furnace and sintered at 1950℃ for 1 hour in an argon atmosphere to achieve ceramic connection, thus obtaining ceramic connectors.
[0083] The intermediate connecting layer of this silicon carbide ceramic connector has a thickness of 9 μm, a flexural strength of 416 MPa at room temperature, and a flexural strength of 362 MPa at 1400 °C. After corrosion with a 6 mol / L NaOH solution at 100 °C for 24 h, the ceramic joint exhibits a weight loss of 3 mg / dm³. 2 After corrosion by 3 mol / L sulfuric acid solution at 100℃ for 24 hours, the weight loss rate was 1 mg / dm³. 2 .
[0084] The silicon carbide ceramic connector in this embodiment can be widely used in aerospace, chemical and heat exchanger packaging fields.
[0085] Compared with Example 2, the difference is that the thickness of the graphite plate is increased in this example, which improves the bending strength and corrosion resistance of the ceramic connector. If the thickness of the graphite plate continues to increase, the bending strength and corrosion resistance will continue to improve, but the rate of improvement will slow down until it stabilizes.
[0086] Example 4
[0087] The universal bonding method for ceramic materials based on passive pressure in this embodiment includes the following steps:
[0088] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first and second ceramic parts. A bonding slurry was obtained by ball milling a mixture of 45g silicon carbide powder (average particle size 40nm), 5g Al4SiC4 sintering aid, 2g polyvinylpyrrolidone, 0.5g polyvinyl butyral, and 50g ethanol for 6 hours. The bonding slurry was then applied to the surface of the first ceramic part using screen printing. The ceramic parts were stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part, with a 10mm thick C / C plate and a 10mm thick titanium boride ceramic plate clamping each side of the sandwich structure. A bonding slurry with a thermal expansion coefficient of 0.5 × 10⁻⁶ was then used. -6 The C / C bolts at / ℃ are clamped and fixed with a preload of 25 N·m. Then, they are placed in a high-temperature sintering furnace and sintered at 1950℃ for 1 hour in an argon atmosphere to achieve ceramic connection, thus obtaining ceramic connectors.
[0089] The intermediate connecting layer of this silicon carbide ceramic connector has a thickness of 12 μm, a flexural strength of 332 MPa at room temperature, and a flexural strength of 278 MPa at 1400 °C. After corrosion with a 6 mol / L NaOH solution at 100 °C for 24 h, the ceramic joint exhibits a weight loss of 12 mg / dm³. 2 After corrosion with 3 mol / L sulfuric acid solution at 100℃ for 24 hours, the weight loss rate was 2.5 mg / dm³. 2 .
[0090] The silicon carbide ceramic connector in this embodiment can be widely used in aerospace, chemical and heat exchanger packaging fields.
[0091] Compared with Example 2, the difference is that this example uses a C / C plate and a titanium boride ceramic plate for clamping. The coefficient of thermal expansion of the titanium boride ceramic plate is less than that of the graphite plate, which leads to a reduction in thermal stress at the connection surface and a decrease in bending strength and corrosion resistance.
[0092] Example 5
[0093] The universal bonding method for ceramic materials based on passive pressure in this embodiment includes the following steps:
[0094] Alumina ceramics were ultrasonically cleaned and dried to serve as the first and second ceramic parts. A bonding slurry was obtained by ball milling 49g of alumina powder (average particle size 40nm), 1g of MgO sintering aid, 2g of polyvinylpyrrolidone, 0.5g of polyvinyl butyral, and 50g of ethanol for 6 hours. The bonding slurry was then applied to the surface of the first ceramic part using screen printing. The ceramic parts were stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part, with a 10mm thick C / C plate and a 10mm thick graphite plate clamping each side of the sandwich structure. A material with a thermal expansion coefficient of 0.5 × 10⁻⁶ was then used. -6The C / C bolts at / ℃ are clamped and fixed with a preload of 25 N·m. Then, they are placed in a high-temperature sintering furnace and sintered at 1450℃ for 1 hour in an argon atmosphere to achieve ceramic connection, thus obtaining a ceramic connector.
[0095] The intermediate connecting layer of this alumina ceramic connector has a thickness of 30 μm, a flexural strength of 340 MPa at room temperature, and a flexural strength of 260 MPa at 1400 °C.
[0096] The alumina ceramic connector in this embodiment can be widely used in semiconductor, chemical and other fields.
[0097] Example 6
[0098] The universal bonding method for ceramic materials based on passive pressure in this embodiment includes the following steps:
[0099] Alumina ceramics were ultrasonically cleaned and dried to serve as the first and second ceramic parts. A bonding slurry was obtained by ball milling 49g of alumina powder (average particle size 40nm), 1g of MgO sintering aid, 2g of polyvinylpyrrolidone, 0.5g of polyvinyl butyral, and 50g of ethanol for 6 hours. The bonding slurry was then applied to the surface of the first ceramic part using screen printing. The ceramic parts were stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part, with a 10mm thick C / C plate and a 10mm thick graphite plate clamping each side of the sandwich structure. A material with a coefficient of thermal expansion of 0.005×10⁻⁶ was then used. -6 The C / C bolts at / ℃ are clamped and fixed with a preload of 25 N·m. Then, they are placed in a high-temperature sintering furnace and sintered at 1450℃ for 1 hour in an argon atmosphere to achieve ceramic connection, thus obtaining a ceramic connector.
[0100] The intermediate connecting layer of this alumina ceramic connector has a thickness of 21 μm, a flexural strength of 383 MPa at room temperature, and a flexural strength of 303 MPa at 1400 °C.
[0101] The alumina ceramic connector in this embodiment can be widely used in semiconductor, chemical and other fields.
[0102] Compared with Example 5, the difference is that in this embodiment, C / C bolts with a coefficient of thermal expansion that is infinitely close to zero are used for clamping and fixing, which further improves the bending strength of the ceramic connector.
[0103] Example 7
[0104] The universal bonding method for ceramic materials based on passive pressure in this embodiment includes the following steps:
[0105] Two boron carbide ceramics were ultrasonically cleaned and dried to serve as the first and second ceramic parts. A bonding slurry was obtained by ball milling a mixture of 45g boron carbide powder (average particle size 40nm), 5g Y₂O₃ sintering aid, 2g polyvinylpyrrolidone, 0.5g polyvinyl butyral, and 50g ethanol for 6 hours. The bonding slurry was then applied to the surface of the first ceramic part using screen printing. The ceramic parts were stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part, with a 10mm thick C / C plate and a 10mm thick graphite plate clamping each side of the sandwich structure. A material with a thermal expansion coefficient of 0.5 × 10⁻⁶ was then used. -6 The C / C bolts at / ℃ are clamped and fixed with a preload of 25 N·m. Then, they are placed in a high-temperature sintering furnace and sintered at 2000℃ for 1 hour in an argon atmosphere to achieve ceramic connection, thus obtaining a ceramic connector.
[0106] The intermediate connecting layer of this boron carbide ceramic connector has a thickness of 11 μm, a flexural strength of 424 MPa at room temperature, and a flexural strength of 383 MPa at 1400 °C.
[0107] The boron carbide ceramic connector in this embodiment can be widely used in fields such as superhard materials, aerospace, refractory materials, and nuclear industry.
[0108] Example 8
[0109] The universal bonding method for ceramic materials based on passive pressure in this embodiment includes the following steps:
[0110] Two titanium diboride ceramics were ultrasonically cleaned and dried, serving as the first and second ceramic parts. A bonding slurry was obtained by ball milling a mixture of 55g titanium diboride powder (average particle size 40nm), 5g borax sintering aid, 1g polyvinylpyrrolidone, 0.5g polyvinyl butyral, and 40g ethanol for 8 hours. The bonding slurry was then applied to the surface of the first ceramic part using screen printing. The ceramic parts were stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part, with a 10mm thick C / C plate and a 10mm thick graphite plate clamping each side of the sandwich structure. A material with a thermal expansion coefficient of 0.5 × 10⁻⁶ was then used. -6 The C / C bolts at / ℃ are clamped and fixed with a preload of 25 N·m. Then, they are placed in a high-temperature sintering furnace and sintered at 1900℃ for 1 hour in an argon atmosphere to achieve ceramic connection, thus obtaining ceramic connectors.
[0111] The intermediate connecting layer of this titanium diboride ceramic connector has a thickness of 22 μm, a bending strength of 146 MPa at room temperature, and a bending strength of 112 MPa at 1400 °C.
[0112] The titanium diboride ceramic connector in this embodiment can be widely used in coatings, refractory materials, cutting tools, and electronic devices.
[0113] Comparative Example 1
[0114] The passive pressure-based ceramic material joining method in this comparative example includes the following steps:
[0115] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first and second ceramic parts. A bonding slurry was obtained by ball milling a mixture of 45g silicon carbide powder (average particle size 40nm), 5g Al2O3-Y2O3 (YAG) sintering aid, 2g polyvinylpyrrolidone, 0.5g polyvinyl butyral, and 50g ethanol for 6 hours. The bonding slurry was then applied to the surface of the first ceramic part using screen printing. The ceramic parts were then stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part. Figure 3 The traditional integrated graphite clamp shown is pre-tightened with a force of 25 N·m, and then placed in a high-temperature sintering furnace. In an argon atmosphere, it is sintered at 1850℃ for 1 hour to achieve ceramic connection, resulting in a ceramic connector.
[0116] The intermediate connecting layer of this silicon carbide ceramic connector has a thickness of 86 μm, a flexural strength of 105 MPa at room temperature, and a flexural strength of 56 MPa at 1400 °C.
[0117] Comparative Example 2
[0118] The universal bonding method for ceramic materials based on passive pressure in this comparative example includes the following steps:
[0119] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first and second ceramic parts. A bonding slurry was obtained by ball milling a mixture of 45g silicon carbide powder (average particle size 500nm), 5g Al2O3-Y2O3 (YAG) sintering aid, 2g polyvinylpyrrolidone, 0.5g polyvinyl butyral, and 50g ethanol for 6 hours. The bonding slurry was then applied to the surface of the first ceramic part using screen printing. The ceramic parts were stacked in a sandwich structure of first ceramic part - bonding slurry - second ceramic part, with a 10mm thick C / C plate and a 10mm thick graphite plate clamping each side of the sandwich structure. A material with a thermal expansion coefficient of 0.5 × 10⁻⁶ was then used. -6 The C / C bolts at / ℃ are clamped and fixed with a preload of 25 N·m. Then, they are placed in a high-temperature sintering furnace and sintered at 1850℃ for 1 hour in an argon atmosphere to achieve ceramic connection, thus obtaining ceramic connectors.
[0120] The intermediate connecting layer of this silicon carbide ceramic connector has a thickness of 35 μm, a flexural strength of 175 MPa at room temperature, and a flexural strength of 156 MPa at 1400 °C.
[0121] Compared with Example 1, the difference is that the average particle size of silicon carbide powder in this comparative example is increased, resulting in a decrease in flexural strength and corrosion resistance.
[0122] In summary, this invention, by adjusting the clamping plate material, the connecting slurry, and the connecting temperature, can meet the connection requirements of various ceramic materials such as oxides, carbides, and borides, and has universal applicability. Furthermore, ceramic connectors made using the passive pressure-based universal ceramic material connection method of this invention have good bending strength and acid and alkali corrosion resistance.
[0123] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.
Claims
1. A universal bonding method for ceramic materials based on passive pressure, characterized in that, The connection method includes: After coating the surface of the first ceramic part with a connecting slurry, the second ceramic part is placed on it and stacked in a sandwich structure of first ceramic part-connecting slurry-second ceramic part. On both sides of the sandwich structure, low thermal expansion coefficient C / C plates and differential thermal expansion coefficient plates are used for clamping and fixed with low thermal expansion coefficient C / C bolts. Then, sintering is performed to achieve the connection. The bonding slurry comprises ceramic powder, sintering aid, dispersant, binder, and solvent; the solid content of the bonding slurry is 30-70 wt%. The thermal expansion coefficient of the C / C plate with a low thermal expansion coefficient is 0~5×10⁻⁶. -6 / ℃; The differential thermal expansion coefficient plate includes one or more of graphite plates, alumina ceramic plates, and titanium boride ceramic plates; the thermal expansion coefficient of the graphite plate is 5 × 10⁻⁶. -6 ~25×10 -6 / ℃; the coefficient of thermal expansion of the alumina ceramic plate is 5.5×10. -6 ~8.9×10 -6 / ℃; the coefficient of thermal expansion of the titanium boride ceramic plate is 6.1×10⁻⁶. -6 ~8.2×10 -6 / ℃; The thermal expansion coefficient of the C / C bolt with a low thermal expansion coefficient is 0~2×10⁻⁶. -6 / ℃.
2. The universal bonding method for ceramic materials based on passive pressure according to claim 1, characterized in that, The thickness of the differential thermal expansion coefficient plate is 1~130mm, and its length and width are both greater than those of the first ceramic part and the second ceramic part; the thickness of the low thermal expansion coefficient C / C plate is 1~130mm, and its length and width are both greater than those of the first ceramic part and the second ceramic part.
3. The universal bonding method for ceramic materials based on passive pressure according to claim 1, characterized in that, The first ceramic component and the second ceramic component are independently selected from one or more of oxide ceramics, carbide ceramics, and boride ceramics.
4. The universal bonding method for ceramic materials based on passive pressure according to claim 1, characterized in that, The ceramic powder has an average particle size of 1~200nm; the sintering aid includes one or more of B4C, carbon black, Al2O3, MgO, Y2O3, Al2O3-Y2O3, AlN, Al4C3-B4C, Al4SiC4, and borax.
5. A ceramic connector, characterized in that, It is manufactured by the universal bonding method of ceramic materials based on passive pressure as described in any one of claims 1 to 4, and includes a first ceramic component, an intermediate connecting layer, and a second ceramic component, wherein the thickness of the intermediate connecting layer is 0.1 to 80 μm.
6. The ceramic connector according to claim 5, characterized in that, The intermediate connecting layer lost less than 30 mg / dm³ after being corroded by a 6 mol / L NaOH solution at 100°C for 24 hours. 2 The intermediate bonding layer lost less than 7 mg / dm³ after being corroded by a 3 mol / L sulfuric acid solution at 100°C for 24 hours. 2 The intermediate connecting layer has a flexural strength of 120~550MPa at room temperature and 80~520MPa at 1400℃.
7. The application of the ceramic connector as described in claim 5 in the fields of aerospace, heat exchanger packaging, semiconductor, coating, refractory materials, and cutting tools.
Citation Information
Patent Citations
Method of connecting sheets by thermal self-pressing
CN103464907A
Connection method of silicon carbide ceramics based on liquid phase sintering
CN114478043A
